1320 Learning how to TODDLE: the building blocks to developing your paediatric portfolio and career. (17th August 2022) - Wang, Jingjing; Blackwood, Clair-Soo; Joseph, Sonia
Abstract : Aims: The need for specialist training in Paediatrics has increased with developing technical complexity and advances in children's medicine. To meet this demand, recruitment and retention in Paediatrics is essential. Early exposure and support to this diverse vocation is warranted. 1–3 Paediatric career advice is rarely discussed at depth, both intra- and extracurricularly. It provides vital support for medical students and doctors pursuing Paediatric careers 4 and provides foundations for career building excellence. This ensures competency in our graduates and applicants as they prepare to treat the children of tomorrow. In order to fill this teaching gap, 'TODDLE: The building blOcks to Developing your paeDiatric portfoLio and carEer' was created by Edinburgh University Paediatrics Society (EUPS). This abstract will define plans for this series and analysis of benefit. TODDLE aims to equip medical students and FYs with knowledge about the career pathway and Paediatric portfolio via a comprehensive set of 5 virtual webinars spanning March to April. The course will run completely free and online for increased accessibility. Tutors will consist of Paediatric trainees and medical students, sharing their experiences and expertise, while facilitating networking and informal mentorship. Methods: Each webinar consists of a 30-minute trainee-led talk and a 15-minute student-led talk, followed by a Q&A. Pre-webinar polls will be used to check attendee understanding, demographics, and opinions. Post-webinar, feedback forms will be sent out to assess factors relating to experience and value of the series, including free-text. To assess course impact we will analyse attendee feedback to quantify usefulness of this series to aspiring Paediatricians. To further enhance the value of this course for participants, attendees of 3/5 webinars will receive a SPHERE-accredited certificate for their portfolios. Results: A preliminary scoping poll at the University of Edinburgh was answered by 9 preclinical and 11 clinical medical students. Primary results ( figure 1 ) found 70% disagreeing that they had enough Paediatric application information from medical school, with survey-goers wanting to learn more about building a competitive Paediatric portfolio/CV, as well as the career/application pathways. We anticipate final results to support the need for more Paediatric career advice to medical students and FYs, and the benefit of a career teaching series. While EUPS strives to support students, improvements in the formal curriculum by medical schools play a key role in nurturing aspiring Paediatricians. Conclusion: Paediatric career building is an important and yet often ignored topic that requires more support in medical education. We have endeavoured to fill this gap extracurricularly with the webinar series TODDLE. Future work should aim to better support medical students interested in Paediatrics by providing formal teaching on career building and portfolios. We hope that the lessons from this series can be brought forward to enhancing the medical curriculum and child health. References: The Journal of Pediatrics, HB Fromme et al Archives of Disease in Childhood - Education and Practice, HM Goodyear European Journal of Pediatrics, T Bindal Medical Education, TW Lambert et al